Mechanical Errors Made by the Second Semester Students of Stie-Sak in Writing Paragraph Academic Year 2024/2025 - Padli, Al (The Future of Education Journal, 2025)
This research was a descriptive research, it was done at second semester of STIE-SAK academic year 2024/2025. The aim of this research was to analyze students’ mechanical errors made by the second semester of STIE-SAK academic year 2024/2025. The population of this study is all of the second semester students of STIE-SAK. There were six classes of the second semester of STIE-SAK. To limit the population, the researcher needed the sample. The sample of this research was chosen by using random sampling or change sampling. By using random sampling, the researcher got the second semester students of Development Economics Major at STIE-SAK as a sample in this research. After analyzing the data, In conclusion, from the students’ score, it was found that the students’ writing paragraph was failed. The students’ average score was 49 %. From the students scoring criteria, there was no students got A, and there were only 4 students got B, 1 students got C, there were 8 students got D, and most of them or 12 students got E. From the explanation above, it was found that the students made errors in punctuation, capitalization and spelling words. In using punctuation, most of them made errors on it. In using capitalization, most of the students made errors. While in using spelling word, there were any of them made errors on the spelling words.